Representation of Load Dynamics in the Dispatch of Primary Reserves [Representacion de la Dinámica de la Carga en el Despacho Déreservas Primarias] - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2016)
The incorporation of renewable energies in electrical systems has led to replace the conventional generation of energy, causing serious problems in the stability and security of the electrical system. This happens as these energies provide limited inertia and speed governor response to the electrical system; consequently, the frequency response has been affected. In addition, the load frequency dynamics tend to moderate these deviations. This study validates a dispatch model of primary reserves for Chile which ensures, through a ramp-constrained, that the frequency deviation after the disturbance has occurred is above a preset value. In addition, the criteria for incorporating the dynamic load to the primary reserve dispatch are established. © 2016 IEEE.